Interactive Book Design as a Development Media Children's Fine Motor Skills at Nusa Ceria Islamic Kindergarten - Natalia, Rissa Prita Natalia Rissa; Kurniawan, Rahmat Kurniawan (IC-ITECHS, 2024)
Early Childhood Education (PAUD) in Indonesia is very crucial, in accordance with Law No. 20 of 2003 which stipulates early childhood as the period from birth to six years. At this stage, early childhood is a golden period, where the child's brain experiences rapid development to support the child's physical and mental development. However, research shows that children at the Nusa Ceria Islamic Kindergarten, Sumberrejo Village, Lumajang Regency, face difficulties in developing fine motor skills, such as delays in activities such as sticking paper or dry leaves. This difficulty is caused by learning methods that rely too much on basic learning. In addition, the lack of opportunities for environmental exploration and overly protective parenting patterns are also inhibiting factors. To overcome this problem, collaboration between educators and parents in providing stimulation through fun activities and creative media is needed. One proposed solution is the use of interactive books designed to improve children's fine motor, cognitive, language, and social skills as a whole. This book is expected to be an effective external impetus in supporting early childhood development.